Comparison of DNA extraction methods for detecting African swine fever virus in feed and environmental samples - Kwon, Taeyong; Gebhardt, Jordan T.; Lyoo, Eu Lim; Jones, Cassandra K.; Trujillo, Jessie D.; Gaudreault, Natasha N.; Richt, Juergen A. (Frontiers in Veterinary Science, 2025)
African swine fever (ASF) is a fatal viral disease of domestic and wild pigs, with mortality rates reaching up to 100%. In the absence of a safe and effective vaccine in non-endemic countries, it is imperative for the swine industry to implement enhanced biosecurity measures to control and prevent ASF outbreaks. Early detection is a key strategy to prevent the introduction of virus (ASFV) into naïve herds and confine the outbreak sites. Despite advanced modern technology for better diagnostics, knowledge regarding ASFV DNA detection in environmental samples is limited. Therefore, this study aimed to compare four DNA extraction methods for ASFV-contaminated feed and environmental samples: two magnetic bead-based extractions, one column-based PowerSoil Pro extraction, and one point-of-care M1 extraction. Three sets of samples were attained from our sample inventory saved from previous ASFV experiments: (1) surface samples contaminated with ASFV and different types of organic matter, (2) ASFV-contaminated feed and feed ingredients, and (3) feed mill surface samples collected during manufacturing of feed inoculated with ASFV. After DNA extraction, quantitative PCR was performed under identical conditions for all samples. ASFV DNA was detected by all four different extraction methods in the first two sets of sample collections. In these samples, significantly lower Cq values (p < 0.05) were detected in two magnetic bead-based extractions compared to the column-based PowerSoil Pro and point-of-care M1 extractions. Similarly, better DNA detection was observed using magnetic bead extractions in the feed mill surface samples. We conclude that all extraction methods evaluated in this study can be used for ASFV DNA detection in feed and environmental samples and higher sensitivity was observed using magnetic bead-based extraction which was also able to detect ASFV DNA in feed mill surface samples collected during manufacturing of ASFV-inoculated feed.